PELANGGARAN PRINSIP KERJASAMA DAN KESANTUNAN BERBAHASA SISWA TERHADAP GURU MELALUI TINDAK TUTUR VERBAL DI SMP MA’ARIF TLOGOMULYO-TEMANGGUNG (KAJIAN SOSIOPRAGMATIK) - Molas Warsi Nugraheni (Universitas Tidar, 2015)
Conversation is verbal interaction that takes place in an order and organized and involves two or more parties in order to achieve certain objectives as a form of communication events. When the conversation does not meet the rules of the communication, failure is diagnosed. Conversation failure was effected due to a violation of the principles of politeness and cooperation. This study was conducted in SMP Maarif Tlogomulyo by analyzing teachers and students conversations in learning process. The results of this research were 1) students did a violate of the maxim of quantity, quality, relevancy, and the thimble way, 2) students did a violate of the principle of politeness in the interaction in the classroom. This was influenced by many factors, particularly the influence of the environment and level of education. Using local utterances was highly recommended to preserve the local culture, but more harmonious when it was used in a good and polite conversation.Keywords : violation of the principle of cooperation, principle of politeness, and verbal speech acts